(untitled) (Revista Nacional de Odontología, 2016)
Introduction: the gummy smile (gs) is one of the most negatively valued aspects; its presence in the adult life is reason of constant consultation, but during childhood it usually is considered normal. The aim of this study was to describe and compare the perio-dontium traits in a group of children with different malocclusions with or without gum-my smile, and evaluate the influence of gingival characteristics along with gummy smile. Methods: in this analytical study of case and control, the sample size was probabilistic. 163 children with mixed silent dentition that meted the criteria of inclusion and exclusion were involved: 37 cases with gummy smile (gs) and 126 controls without gummy smile (ngs). The occlusal variables of smile and periodontal disease were assessed through a cli-nical exam and photograms. The evaluators were previously calibrated (kappa 0,87 and icc0,96). Results: the average age of patients in both groups was of 8,8 years with a standard deviation of 0,9 in cases and 0,8 in controls. The prevailing malocclusion was class I (63,8% of the samples). The periodontal characteristics were similar in both groups. The thick periodontal biotype had a tendency to behave as risk factor to gs (or 1,6) but the relation wasn’t statistically significant (ic = 95% 0,6 – 4,1). Conclusion: the periodontal factors do not have an effect on gummy smile in children, though their behavior at later stages must be closely observed